Sistem Pemetaan Geografis Jalan Rusak Berbasis Mobile Menggunakan Location Based Service Studi Kasus Kota Malang - Ilham Rachmad Zunaidi; Tri Afirianto; Komang Candra Brata (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Increasing the population in Malang there are several sectors such as education, tourism and employment. The increase in population was also followed by an increase in the number of vehicles by 567,719 including public and private transportation. A woman had been a victim of an accident and died in Lowokwaru District due to avoiding potholes. The community hopes that repairs to potholes will be carried out immediately by the relevant parties. Roads in Malang are the responsibility of the Public Works and Spatial Planning Office of Malang City, which must record and repair damaged roads, but in recording damaged roads it is still done manually by recording in a book that contains street addresses without knowing the exact position of the location. Mobile based application for Public Works and Spatial Planning Officers of Malang City can see the distribution of damaged roads in Malang City and map the damaged roads by taking latitude and longitude coordinates according to the location chosen by the officers and utilizing location based services, namely global positioning system sensor. System development uses extreme programming methods to anticipate if there are changes in user needs. The results of tests conducted, functional testing, compatibility testing on several OS android, and usability testing of system usability scale equations obtained a value of 67.3 with adjective ratings = good.